Sukuk Performance Using Comparison of Return and Risk Through Calculation of Market Price and Fair Price - Adieb Mursyada; Fifi Swandari (International Journal of Emerging Issues in Islamic Studies, 2021)
Sukuk investors’ important information used by investors of Sukuk (proof or claim of ownership on assets) is the market price of the Sukuk issued by the IDX and the fair price of the Sukuk issued by the Indonesian Securities Price Appraiser (PHEI). This is a signal or initial information for investors in considering the decision to invest in Sukuk. The measured performance returns as measured by Holding Period Yield (HPY), Yield to Maturity (YTM), and Sharpe Index, while Risk of Sukuk is measured based on its standard deviation. Corporate Sukuk are classified into financial and nonfinancial sectors and have short, medium, and long maturities. Comparative analysis is conducted using an Independent Sample t-test and ANOVA. The results showed that the average Sukuk return was calculated at a higher market price than the fair price. Sukuk return results in a pattern of movement that tends to be inversely proportional to the market price or fair price of the Sukuk, while the risk of Sukuk based on price issuing institutions had a movement pattern that tends to be in the same direction as the price. Furthermore, corporate Sukuk in the non-financial sector had a higher average return but was more susceptible to risk than the financial sector. Corporate Sukuk with long maturities had a higher average yield and risk exposure than medium and short-term Sukuk. Hypothesis testing showed a significant difference between the market price and the fair price of corporate Sukuk.